Failure to launch - J. Dara Bloom; David Yates; Gizem Templeton; Emma Brinkmeyer; Caroline Hundley (Journal of Agriculture, Food Systems, and Community Development)
The majority of children ages 0–5 consume most of their meals in early care and education (ECE) settings, prompting interest in the nutritional quality of childcare meals and snacks as a vehicle for improving dietary-related health outcomes for this vulnerable population.[1] Our team has identified central kitchens that serve prepared meals to childcare centers as a potential model to improve meal quality for children, while also relieving childcare providers of the burdens of meal preparation and paperwork associated with federal meal reimbursements, and aggregating local food purchases to create a larger market for farmers than purchases by individual centers. Our team partnered with a funder, a church, and community organizations to attempt a pilot that would replicate this central kitchen model in a rural area. Unfortunately, the pilot project was never fully realized, leading us to conduct a process evaluation to identify the generalizable factors that impeded its success. We identified four key factors, including the underlying power dynamic between the funder and recipient, reliance on a single project champion, lack of buy-in from community stakeholders, and failure to involve the county health department early in the planning process. In this paper, we construct a timeline of the project to help identify key factors that led to the project’s failure to launch, explain our four key findings, and provide a set of recommendations that funders and other communities can take into consideration as they consider the viability of this timely intervention.